Essays in economics and other cheerful themes a dismisal scientist's occasional reflections on the world around him - Subramanian, S (Sage, 2014)
Essays in economic and other cheerful themes is a collection of pieces on economy, polity and society, written by a social scientist over a number of years. The book addresses conceptual and empirical issues in development at both national and global levels. The philosophical bases of these issues are sought to be addressed in relatively non-technical and accessible terms. The book also makes space for essays that deal with less solemn phenomena, such as cricket, film, the conduct of academic institutions, and the esoteric excesses of scholarly writing in the social sciences and humanities. The book is something of a professional economists's ramble through territory that is both familiar and important to him, but undertaken in a spirit of some leisureliness which the author hopes will attract a readership beyond that, solely, of fellow-professionals.